Asymmetric anionic polymerizations of 7‐(o‐substituted phenyl)‐2, 6‐dimethyl‐1, 4‐benzoquinone methides: Electrostatic interaction and steric, inductive, and resonance effects of the ortho‐substituent on the optical activity. Issue 6 (15th March 2017) - Uno, Takahiro; Yamamoto, Shuhei; Yamane, Atsushi; Kubo, Masataka; Itoh, Takahito
ABSTRACT: 7‐( o ‐Substituted phenyl)‐2, 6‐dimethyl‐1, 4‐benzoquinone methides which have an electron‐donating methoxy‐( o ‐OMe, 2a ) and methyl‐ ( o ‐Me, 2b ) substituents or an electron‐withdrawing cyano‐ ( o ‐CN, 2c ) and trifluoromethyl‐ ( o ‐CF3, 2d ) substituents at the ortho ‐position of the aromatic ring and 7‐( m ‐substituted phenyl)‐2, 6‐dimethyl‐1, 4‐benzoquinone methide with an electron‐withdrawing trifluoromethyl‐ ( m ‐CF3, 2e ) substituent at the meta ‐position of the aromatic ring were synthesized, and their asymmetric anionic polymerizations using the complex of lithium 4‐isopropylphenoxide with (−)‐sparteine were carried out in toluene at 0 °C. The polymers with negative optical activity were obtained for all of five monomers, and their specific rotation values largely changed depending upon the substituents of the monomers. On the basis of the comparison of various substituents effects, it was found that the specific rotation of obtained polymers is significantly affected by the electronic effects such as inductive and resonance effects rather than the steric and electrostatic effects of the substituent. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1048–1058 Abstract : Asymmetric anionic polymerizations of 7‐( o ‐substituted phenyl)‐2, 6‐dimethyl‐1, 4‐benzoquinone methides (R = o ‐OMe (2a ), o ‐Me (2b ), o ‐CN (2c ), and o ‐CF3 (2d )) and 7‐( m ‐trifluoromethylphenyl)‐2, 6‐dimethyl‐1, 4‐benzoquinone methide (R = m ‐CF3 (2e )) using the complex of lithium 4‐isopropylphenoxide with (−)‐sparteine gave corresponding polymers with negative specific rotation, and the specific rotation value of obtained polymers were not affected by electrostatic and steric effects, but significantly affected by the balance of inductive and resonance effects of substituent.